Epstein-Barr virus with heterogeneous DNA disrupts latency. - Miller, G (1984)
By cloning the HR-1 Burkitt lymphoma line, we previously uncovered two distinct biological variants of nontransforming Epstein-Barr virus (EBV). The most commonly cloned variant has a low rate of spontaneous viral synthesis and is unable to induce early antigen in Raji cells (EAI-). A rare variant spontaneously releases virus which is capable of inducing early antigen in Raji cells (EAI+). Since EAI- virus lacks heterogeneous DNA (het-) and EAI+ virus contains heterogeneous DNA (het+), we suggested that spontaneous viral synthesis and induction of early antigen are biological properties which correlate with the presence of het sequences. The present experiments provide three new lines of experimental evidence in favor of this hypothesis. (i) Revertant subclones of the EAI+ het+ variant which have lost the het DNA concomitantly lost EAI ability. Thus, het DNA is not stably associated with the cells as are the episomes. (ii) het DNA was acquired by two het- subclones of the HR-1 line after superinfection with EAI+ virus. After superinfection, these clones synthesized EAI+ het+ virus. Thus, het DNA may be maintained in the HR-1 line by cell-to-cell spread. (iii) Virus with het DNA activated full expression of endogenous latent EBV of the transforming phenotype in a line of immortalized neonatal lymphocytes designated X50-7. By use of restriction endonuclease polymorphisms unique to both the superinfecting and endogenous genomes, we show that the genome of the activated virus resembles that of the virus which was endogenous to X50-7 cells. This result suggests that het sequences result in transactivation of the latent EBV. het DNA had homology with EBV sequences which are not normally contiguous on the physical map of the genome. het DNA was always accompanied by the presence of DNA of nonheterogenous HR-1. Thus, het DNA is a form of "defective" EBV DNA. However, the biological effect of this defective DNA is to enhance rather than to interfere with EBV replication. This is a novel property of defective virus.